2022
DOI: 10.1002/mame.202200128
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐Terminated Hyperbranched Polymer‐Based Recyclable Elastic Fibers for a Breathable and Antibacterial Triboelectric Nanogenerator

Abstract: Realizing recyclable triboelectric active materials with commendable elasticity, breathability, and durable antibacterial performance is significant for the sustainable development of wearables and bioelectronics. A spinnable elastic polymer (MPVA) is developed by modifying polyvinyl alcohol (PVA) with amino-terminated hyperbranched polymers (HBP-NH 2 ), demonstrating a junction-reinforced electrospun nanofiber membrane (MPVA) with lower Young's modulus and improved stretchability, which exhibits robust networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…TENG shows the merits of extensive material options and relatively higher power output. [184,[230][231][232] Xiong et al reported a wearable textile-TENG through dip-coating of black phosphorus and hydrophobic cellulose oleoyl ester nanoparticles (HCOENPs) on polyethylene terephthalate (PET) fabric, skin contacts can trigger the device to harvest biomedical energy. [203] As shown in Figure 5b, the device showed instantaneous maximum output voltage and current density is 880 V and 1.1 μW cm −2 , which maintained stable performance regardless of subjecting to extreme bending, twisting, stretching, and washing.…”
Section: Nonwovenmentioning
confidence: 99%
See 1 more Smart Citation
“…TENG shows the merits of extensive material options and relatively higher power output. [184,[230][231][232] Xiong et al reported a wearable textile-TENG through dip-coating of black phosphorus and hydrophobic cellulose oleoyl ester nanoparticles (HCOENPs) on polyethylene terephthalate (PET) fabric, skin contacts can trigger the device to harvest biomedical energy. [203] As shown in Figure 5b, the device showed instantaneous maximum output voltage and current density is 880 V and 1.1 μW cm −2 , which maintained stable performance regardless of subjecting to extreme bending, twisting, stretching, and washing.…”
Section: Nonwovenmentioning
confidence: 99%
“…TENG shows the merits of extensive material options and relatively higher power output. [ 184 , 230 , 231 , 232 ] Xiong et al. reported a wearable textile‐TENG through dip‐coating of black phosphorus and hydrophobic cellulose oleoyl ester nanoparticles (HCOENPs) on polyethylene terephthalate (PET) fabric, skin contacts can trigger the device to harvest biomedical energy.…”
Section: Elastic Fibers/fabrics For Wearablesmentioning
confidence: 99%
“…Functional designs by means of chemical modification have great progress in the enhancement of electrical properties and extension of hydrophobicity for electrospun nanofibers for TENGs. [66,283] These methods are expected to be used for microspheres and hierarchically structured materials. Furthermore, multilayer assembly of electrospun materials with complementary properties can significantly improve their barrier or penetration, [81,93] and Janus film via specific electrospinning process (e.g., water-assisted electrospinning, [269] side-by-side electrospinning, [284] etc.)…”
Section: Further Functional Designmentioning
confidence: 99%
“…Various functional materials and processing methods have been exploited for SCCFs fabrication, aiming to develop fibers with higher stretchability and conductivity, which are important for wearable devices that require high mechanical compliance and electrical stability. [194][195][196] For various wearable devices, SCCFs could be used as electrodes or sensing modules, serving devices such as sensors, energy harvesters, storage, actuators, heaters, displays, etc. As the improvement of SCCFs performances, increasing efforts are focused on the integration of different fiber-based devices to develop functional platforms or systems for providing more safe and friendly interface devices for wearables and human-machine interactions.…”
Section: Sccfs For Wearablesmentioning
confidence: 99%